The construction of Rural Education policy in the State of Paraná: analysis based on documents - Sandra Garcia Neves; Fabiana Fátima Cherobin; Edilaine Aparecida Vieira (Revista Brasileira de Educação do Campo)
In this study we aim to address the standardization of the Rural Education (EdC) policy in the State of Paraná. To this end we developed bibliographic and documentary research limited to the descriptors “Rural Education”, “Rural Schools” and “State of Paraná”. We problematize the effects of the standardization by the State of Paraná considering its historical constitution with the Landless Workers Movement (MST) and the closure of the EdC. Among the results we highlight that the Statistical Synopses of Inep prove that the number of enrollments, teaching positions and educational establishments in the EdC decreased significantly between 2010 and 2022. We problematize, in our final considerations, that policies such as the implementation of EJA and school transportation programs do not guarantee the right of access to school education for the people of the countryside, waters and forests. Finally, we highlight that the regulation of the EoC does not guarantee the existence of these schools, which imposes the need to fight for the maintenance and quality of the Rural Schools, especially by members of social movements in Paraná.